Thermal treatment of OSB panels: a systematic and bibliometric overview - Sugahara, Estefani Suana [UNESP]; Arroyo, Felipe Nascimento; de Campos, Cristiane Inácio [UNESP]; Botelho, Edson Cocchieri [UNESP]; Christoforo, André Luis; Costa, Michelle Leali [UNESP]; Lahr, Francisco Antonio Rocco (Springer Nature, 2022)
Given the need for durable and low-maintenance products, thermal modification has emerged as an environmentally friendly alternative, replacing chemical treatments. Although the literature reports a large number of articles related to the wood thermal treatment, nevertheless there is a much smaller number related to the thermal treatment of Oriented Strand Board (OSB) panels, which are scarce, limited or contradictory. This panel is used as a building material for internal and covered exterior functions in roofs, walls, floors, structural elements and other uses, currently being widely studied. Therefore, this research aims to present a bibliometric and systematic literature review on heat treatment of OSB panels published between 2000 and 2020 in the Scopus database, through extensive bibliographic review and using a simple and integrative systematic, containing its metrics and main findings. It was found that, despite the progressive growth of interest from the scientific community in relation to wood modification, thermal-based modifications still have much less studies compared to other techniques. At the end, gaps, opportunities and potential areas for future research related to thermal modification of panels are presented.